Delayed Disaster Impacts on Academic Performance of Primary School Children. Issue 4 (24th January 2019) - Gibbs, Lisa; Nursey, Jane; Cook, Janette; Ireton, Greg; Alkemade, Nathan; Roberts, Michelle; Gallagher, H. Colin; Bryant, Richard; Block, Karen; Molyneaux, Robyn; Forbes, David
Abstract : Social disruption caused by natural disasters often interrupts educational opportunities for children. However, little is known about children's learning in the following years. This study examined change in academic scores for children variably exposed to a major bushfire in Australia. Comparisons were made between children attending high, medium, and low disaster‐affected primary schools 2–4 years after the disaster ( n = 24, 642; 9–12 years). The results showed that in reading and numeracy expected gains from Year 3 to Year 5 scores were reduced in schools with higher levels of bushfire impact. The findings highlight the extended period of academic impact and identify important opportunities for intervention in the education system to enable children to achieve their academic potential.